New species and records of Filistatidae (Arachnida: Aranei) from Iran - Zamani A; Marusik YM (KMK SCIENTIFIC PRESS LTD, MOSCOW STATE UNIV, 2022)
Three new species of Filistatidae are described from Iran: Microfilistata magalhaesi sp.n. (male, Isfahan Province, central Iran), Zaitunia darreshurii sp.n. (female, Lorestan Province, southwestern Iran) and Z zagrosica sp.n. (female, Kohgiluyeh & Boyer-Alunad Province, southwestern Iran). Microfilistata Zonstein, 1990 is recorded from Iran for the first time, and its record lies at the southwesternmost limits of the generic range. Hitherto, the genus included two species described from Uzbekistan and Turkmenistan. New records are provided for Filistata lehtineni Marusik et Zonstein, 2014 and Zaitunia akhanii Marusik et Zamani, 2015, representing the southernmost localities of the species ranges. Collecting localities of Microfilistata and all the Filistatidae occurring in Iran are mapped.